Multiple-use water services: climbing the water ladder - van Koppen, Barbara; Smits, S. (Practical Action Publishing, 2010)
This article presents findings of the action-research project on the what, why and how of 'multiple-use water services' or MUS, supported by the Challenge Program on Water and Food (active in 30 sites in 8 countries in Latin America, Africa and Asia). The consortium of partners from the domestic and productive water sectors pioneered the implementation of two models of MUS on the ground: homestead-scale MUS and community-scale MUS. Further, through learning alliances of 150 institutions, the project pilot-tested ways to scale-up MUS among intermediate- and national-level water service providers. Key lessons for scaling up by water users' movements, NGOs, the domestic sector, the productive sector and local government are discussed. Also in the light of the growing recognition of MUS across the globe, further innovation and implementation at scale are warranted to tap the many identifi ed opportunities of MUS compared with single-use approaches.